RELEVANSI KONSEP HIJAB DALAM PEMIKIRAN SYAIKH ALI ASH-SHOBUNI DI ERA KONTEMPORER - Mukorobin, Diya'ul; Kaminah, Lilik Iski (Muta'allim: Jurnal Pendidikan Agama Islam, 2025)
The relevance of the concept of hijab in Sheikh Ali Ash-Shobuni's thought in the contemporary era reflects the dynamics between religious obligations and the evolving social context. In his work,